Neighborhood Blight, Stress, and Health: A Walking Trial of Urban Greening and Ambulatory Heart Rate - South, Eugenia C. (Am J Public Health, 2015)
We measured dynamic stress responses using ambulatory heart rate monitoring as participants in Philadelphia, Pennsylvania walked past vacant lots before and after a greening remediation treatment of randomly selected lots. Being in view of a greened vacant lot decreased heart rate significantly more than did being in view of a nongreened vacant lot or not in view of any vacant lot. Remediating neighborhood blight may reduce stress and improve health.